2017
DOI: 10.1515/orga-2017-0010
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors in the Development of Low Back Pain Among Professional Drivers

Abstract: Background and purpose: Professional drivers as a group are exposed to high risk of developing low back pain due to ergonomic factors and work conditions. The purpose of the study was to examine to what extent the low back pain occurs among Slovene professional drivers as a result of the development of various psychosocial factors. Methodology: The study involved 275 respondents (professional bus drivers, car/van drivers, international truck/ lorry drivers, and ambulance car drivers). Hypotheses were tested us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
4
0
3
Order By: Relevance
“…Occupational health has been a major cause of worry in the driving profession particularly among three-wheel drivers [6,7]. Bajaj is among one of the most important modes of within-city transport system, relatively inexpensive, easily accessible, and an emerging job opportunity in most parts of developing countries [8] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Occupational health has been a major cause of worry in the driving profession particularly among three-wheel drivers [6,7]. Bajaj is among one of the most important modes of within-city transport system, relatively inexpensive, easily accessible, and an emerging job opportunity in most parts of developing countries [8] (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Due to exposure to magnetic fields train engine drivers are group of professional drivers with excess risk of cancer incidence, particularly brain tumors and leukemia (Bilban, 2016). Authors also found exposure association with leukemia and Hodkin's disease (Kresal et al, 2017).…”
Section: Introductionmentioning
confidence: 93%
“…Professional drivers are also exposed to high blood pressure and cardio vascular system diseases due to insufficient blood supply to the lower part of the body caused by prolonged sitting. In addition, professional drivers are often exposed to the locomotor system diseases, for instance the lower spine, as well as to psychological problems (Louit-Martinod et al, 2016; Kresal et al, 2017). Despite the fact that train engine driver is a profession that is seemingly comparable to similar professions in the transport sector, it is associated with specific risks that have a significant impact on their physical and physical health.…”
Section: Introductionmentioning
confidence: 99%
“…Kresal et al refieren que el dolor lumbar en conductores profesionales, es causado principalmente por levantar y transportar cargas pesadas, condiciones de trabajo inadecuadas, mala condición física, salidas nocturnas regulares, trabajo por turnos y estrés 27 .…”
Section: Salud: Enfermedades Músculo Esqueléticas Trastornos De Salud Mental Y Violenciaunclassified
“…Diversos artículos, señalan que una de las grandes afecciones relacionadas con el tipo de trabajo en este caso, son las enfermedades musculo-esqueléticas, especialmente el dolor lumbar asociado a una mala postura durante la extensa jornada 24,25,26 . La presencia de este tipo de patologías perjudica la labor del trabajador y a la vez se traduce en dificultades personales, ausentismo laboral, sentimientos de angustia y disminución notoria de la funcionalidad 27,28 . De igual manera, destacan las problemáticas de salud mental, las cuales han aumentado en los últimos años, y estarían asociadas al alto grado de presión, al acelerado ritmo de trabajo, la fatiga, el cansancio, estrés, malas remuneraciones, extensas jornadas laborales.…”
Section: E-issn: 2346-3414unclassified